Phytochemical screening and antibacterial activity determination of peperomia pellucida extract - Ibrahim, Maizatul Akma; Mohamed Yahaya, Nor Ashikin (Zibeline International Publishing, 2020)
Antibiotics play a vital role in combating diseases caused by pathogenic bacteria. Consumption of antibiotics may emit certain undesirable side effects. Hence, there is an initiative to discover new novel natural products with therapeutic potential, which is safer and can combat various ailments. Peperomia pellucida, which belongs to Piperaceae family, is a herbal plant that can be found in many regions of tropical Asia. This study aimed to extract P. pellucida and screen its phytochemical compositions, and finally test its antibacterial activity on gram positive and gram-negative bacteria. Ethanolic extraction was conducted to obtain a crude extract of the leaf sample. Phytochemical test screenings were also carried out. Antibacterial assay by agar well diffusion was done for the antibacterial activity to determine the minimum inhibitory concentration (MIC). The results showed that the ethanolic leave extract of P. pellucida contains steroids and tannins. The extract exhibited the maximum inhibition zones of 15.67 ± 0.58 mm, 9.67 ± 1.58 mm and 10.67 ± 0.58 mm against E. coli, P. aeruginosa and S. aureus respectively. Based on the MIC test, the ethanolic leaf extracts have shown potential antibacterial activity.